Rapid Radiometric Method of Testing Susceptibility of Mycobacteria and Slow-Growing Fungi to Antimicrobial Agents - Benitez, Pamela (1974)
[(3)H]uracil incorporation into the ribonucleic acid (RNA) of mycobacteria and [(3)H]guanine incorporation into the RNA of fungi were used as measures of cell viability in the presence of several antimicrobial agents. There appeared to be an excellent correlation between traditional susceptibility tests, which required 1 to 4 weeks, and tests of the inhibition of incorporation of RNA precursors, which were completed in 4 to 48 h. The radiometric method may be useful in rapidly determining the susceptibility of slow-growing organisms to antimicrobial agents.